FAUNA AND PLANT NUTRITION OF BED-BUGS BELONGING TO THE FAMILY OF MIRID (MIRIDAE) FOUND IN COTTON, ALFALFA, VEGETABLE AGROCENOSES AND NATURAL ECOSYSTEMS OF THE AMUDARYA AND KHODJAYLI DISTRICTS OF THE REPUBLIC OF KARAKALPAKSTAN - Baltabaev Adamboy Sadullaevich; Makhmudova Mamlakat Mirganievna; Tugizov Ma’rif Bazar ugli; Alieva Durdona Shukururilla kizi; Mahamatjanova Robiya Kamoliddin kizi (European Journal of Agricultural and Rural Education, 2022)
This article presents the vegetation and species composition, seasonal dynamic distribution, phenogram of cannabis belonging to the family Mirid (Miridae), which occurs in cotton, alfalfa and vegetable agrobiocenoses and natural ecosystems of agricultural crops in the Amudarya and Khodjayli districts of the Republic of Karakalpakstan. The nutrition and damage caused by the reproductive organs of the cotton plant have been identified. Cotton and alfalfa plants have been found to reproduce naturally and produce several generations. It has been found to cause great damage to cotton and alfalfa, as well as vegetable crops. Thus, it causes great damage to cotton, alfalfa and vegetable crops, reduces their productivity and causes great damage to the economy of our country